Biosurfactant activity of indigenous Bacillus sp. ES4.3 isolated from endemic breeding sites of dengue hemorrhagic fever vector in Surabaya, East Java, Indonesia: Biosurfactant Activity Bacillus sp. ES4.3 Indonesia (Biodiversitas Journal of Biological Diversity, 2021)
Abstract. Nafidiastri FA, Susetyo RD, Nurhariyati T, Supriyanto A, Geraldi A, Ni’matuzahroh, Fatimah, Salamun. 2021. Biosurfactant activity of indigenous Bacillus sp. ES4.3 isolated from endemic breeding sites of dengue hemorrhagic fever vector in Surabaya, East Java, Indonesia. Biodiversitas 22: 5375-5381. Bacillus spp. have shown the ability to results a variety of commercial bioactive compounds such as proteins, peptides, and lipopeptides (LPs). Some of the LPs produced by Bacillus spp. are surfactin, iturin, and fengicin. This study aimed to determine the name of the indigenous Bacillus sp. ES4.3, the biosynthesis surfactin gene, and the potential activity for biosurfactant produced by entomopathogenic Bacillus sp. ES4.3 isolated from endemic breeding sites of ??Dengue Hemorrhagic Fever Vector in Surabaya, East Java, Indonesia. Genomic DNA of Bacillus sp. ES4.3 was detected by isolating the DNA and visualizing it by electrophoresis. Furthermore, the 16S rRNA gene was amplified by the Polymerase Chain Reaction (PCR) method. The resulting nucleotide sequences were analyzed to find the relationship between Bacillus sp ES4.3 with another bacteria using MEGA version 6 software. Detection of biosynthesis surfactin gene was carried out by PCR method using srfAD primers. Analysis of the homology level of the surfactin gene was performed using the NCBI BLASTn and BLASTp genetic analysis program. The indigenous Bacillus sp. ES4.3 had 97.66% closeness to the species Bacillus velezensis FZB42 and the surfactin gene showed a 100% ID with the surfactin biosynthesis thioesterase SrfA-D gene on the Bacillus amyloliquefaciens group. The biosurfactant activity was indicated by the formation of clear zones, emulsions, and a decrease in surface tension in the values ??of 21.38 mN/m from the NB medium control and 33.74 mN/m from the distilled water control. The ability of B. velezensis ES4.3 to hemolyzed and reduce surface tension indicated the presence of biosurfactant that can disrupt stability and damage the midgut of Aedes aegypti. Thus, B. velezensis ES4.3 has the potential to be developed as a biocontrol in disease vectors.
Keywords: Bacillus sp., 16S rRNA, surfactin, hemolytic activity, emulsification activity, surface tension